Extent of Improvement in the Production of Gram Among the Beneficiaries of NFSM in Southern Rajasthan - Khatik, Ramlal; Sharma, F. L.; Jain, H. K. (Indian Journal of Extension Education, 2017)
The present study was conducted at Banswara and Udaipur districts of Southern Rajasthan. Total eighty NFSM gram  beneficiary farmers were selected on the basis of random sampling method from the identified districts. From the study it  was found that out of the 80 respondents before initiation of NFSM, 41 respondents were categorized in low level of yield  of gram, whereas 33.75 respondents were placed in medium yield category and only 12 respondents possessed high level  of yield of gram. Whereas after initiation of NFSM project, 50.00 per cent respondents could be placed under medium  level of increase in yield group. It was further noted that only 8 (10.00%) gram growers and 32 (40.00 %) respondents  possessed high level of increase in yield of gram crop.
Keywords: NFSM; beneficiary; improvement; production and yield